Digital and Multimedia Organizations in Avestan Studies - Saba Latifpour (تاریخ ادبیات)
Abstract: In this paper we discuss the necessity of presenting a new version of Avesta, the old text and Zoroastrian holly book. We also try to present and compare the ongoing studies in the field of digitalize this book with the aim of representing a new edition. Through observation, collation and analysis, we use historical-descriptive method in this article; we also will present two main institutes that are studying on digitalize the Avestan versions. The two mentioned institutes are located in London and Berlin and numerous Institutions and individuals are collaborating in these extensive studies. Current researches in this field at these two universities has similarities and differences that Some of them will also be considered. Such a big project faces several obstacles and aiming a new Version of Avesta book is confronting deferment and difficulties; but it is hoped that cooperation of scholars in this field facilitates this process.